A Descriptive Analysis of the Indications for Caesarean Section in Lumbini Zonal Hospital, Butwal - Acharya, Shreedhar; Raut, Bhaktabatsal (Journal of Universal College of Medical Sciences, 2018)
AIM: This study was done to find out the incidence and to analyse the various indications for caesarean sections at Lumbini Zonal Hospital. MATERIALS & METHODS: This was a hospital based retrospective study done at Lumbini Zonal Hospital, Butwal. The case files of all the women who had caesarean delivery over the period of one year from 2071/4/1 to 2072/3/32 were reviewed. Various indications of caesarean sections were analysed for the incidence, age, parity, elective vs emergency caesareans. RESULTS: Out of 7589 deliveries, 1316 (17.34%) had caesarean section. Most common indications were previous caesarean 275 (20.89%), non progress of labour 245 (18.61%), cephalopelvic disproportion 222 (16.86%), fetal distress 215 (16.33%), etc. Majority of caesarean 1226 (93.16%) was done in the age group of 20-30yrs, primipara 702 (53.34%), and elective caesarean sections 766 (58.2%). CONCLUSION: Caesarean section rate at Lumbini Zonal Hospital was optimal. Most common indication was repeat caesarean. The overall reduction in caesarean section rate can be met through reduction of elective caesarean with the promotion of trial of labour.Study also concludes that there is a relation between working duration and health problems, and the problems increase as the duration at work increases. Journal of Universal College of Medical Sciences, Vol. 5, No, 2, 2017, Page: 31-34